2002
DOI: 10.1038/sj.mp.4001124
|View full text |Cite
|
Sign up to set email alerts
|

Reelin gene alleles and susceptibility to autism spectrum disorders

Abstract: A polymorphic trinucleotide repeat (CGG/GCC) within the human Reelin gene (RELN) was examined as a candidate gene for autism spectrum disorders (ASDs). This gene encodes a large extracellular matrix protein that orchestrates neuronal positioning during corticogenesis. The CGG-repeat within the 5Ј untranslated region of RELN exon 1 was examined in 126 multiple-incidence families. The number of CGG repeats varied from three to 16 in affected individuals and controls, with no expansion or contraction observed dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
107
0
7

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(123 citation statements)
references
References 29 publications
7
107
0
7
Order By: Relevance
“…The samples differ slightly in the realization of rare alleles, but that is to be expected. In contrast, Zhang et al [2002], in a family-based association study of 126 multiplex families, did find that larger RELN alleles (!11 repeats) were preferentially transmitted to affected children. This study also reported that subjects with delayed speech tended to have one or more of the larger alleles ( 11 repeats).…”
Section: Discussionmentioning
confidence: 86%
“…The samples differ slightly in the realization of rare alleles, but that is to be expected. In contrast, Zhang et al [2002], in a family-based association study of 126 multiplex families, did find that larger RELN alleles (!11 repeats) were preferentially transmitted to affected children. This study also reported that subjects with delayed speech tended to have one or more of the larger alleles ( 11 repeats).…”
Section: Discussionmentioning
confidence: 86%
“…region before the start codon, have reached conflicting results. [43][44][45][46][47][48][49] This may reflect only the common pattern of nonreplication of early claims from small studies 50 or a modest effect may still be present. A large study should be conducted on this association.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies did find an association, [176][177][178] five other studies of comparable size and power did not find an association of the 5 0 UTR trinucleotide or other variants with AD. [179][180][181][182][183] The first positive finding 176 reported an association with the relatively rare longer alleles ( > 10) of the 5 0 UTR trinucleotide polymorphism with AD. However, in another study, 178 the most common repeat 10 was over-represented in AD.…”
Section: Chromosomementioning
confidence: 99%